Prevalência e fatores associados à prescrição/solicitação de suplementação alimentar em recém-nascidos - Ferreira PINHEIRO, Josilene Maria; Brito MENÊZES, Taiana; Fernandes BRITO, Kátia Maria; Lucena de MELO, Andressa Názara; Marques QUEIROZ, Dayanna Joyce; Mattos SUREIRA, Thaiz (Revista de Nutrição, 2023)
Objective To identify the prevalence of infant formula use and assess the characteristics, requesters, and reasons that justify its use in a Baby-Friendly Hospital. Methods This cross-sectional study included 113 mother/child dyads from a university hospital with the title “Baby-Friendly Hospital” from August 2012 to February 2013. A structured questionnaire collected sociodemographic data, obstetric history, newborn birth conditions, infant formula characteristics, and prescribers. Descriptive and inferential analyses (Pearson’s Chi-square test) were conducted using a significance level of p≤0.05 and a 95% confidence interval. Results The prevalence of infant formula prescription was of 16.0%, with smaller adherence in infants born in the first hours of the day (p=0.006). Nurses made the most requests (54.0%) and in the shortest period of time (1 to 6 hours) after delivery (p=0.05). Only 6.2% of the requests complied with the recommendations made by Baby-Friendly Hospitals, and the main reason for the request was hypogalactia (71.7%). Infant formula was more likely to be indicated to infants born by cesarean section (p<0.02). Conclusion Despite the title “Baby-Friendly Hospital”, numerous unnecessary and hasty infant formula indications were identified, which may hinder breastfeeding and favor early weaning, suggesting that the care team needs to assess infant formula indication more thoroughly.